2021
DOI: 10.1371/journal.pone.0255446
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of gut microbiota in people with obesity

Abstract: Background Obesity is the cause of cardiovascular diseases and other diseases, leading to increased medical costs, and causing a great burden to individuals, families and society. The prevalence of obesity is increasing and has become a global health problem. There is growing evidence that gut microbiota plays an important role in obesity. In this article, we revealed the differences in the gut microbiota between 21 people with obesity and 21 control subjects, and predicted the functional potential changes by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 47 publications
9
62
0
Order By: Relevance
“…Studies have reported controversial data about the Firmicutes/Bacteroidetes ratio and the proportion of Firmicutes and Bacteroidetes in obesity. The present data were in agreement with many other studies in China [22], United Kingdom [23], and Canada [24] where insignificant differences in Firmicutes to Bacteroidetes ratio was observed between lean and obese individuals, other studies found that the gut microbiota of obese people is characterized by an increase in the Firmicutes/Bacteroidetes ratio; as in Ukraine [25] and Italy [26]; while others even find an opposite relationship; as in China [27].…”
Section: Discussionsupporting
confidence: 93%
“…Studies have reported controversial data about the Firmicutes/Bacteroidetes ratio and the proportion of Firmicutes and Bacteroidetes in obesity. The present data were in agreement with many other studies in China [22], United Kingdom [23], and Canada [24] where insignificant differences in Firmicutes to Bacteroidetes ratio was observed between lean and obese individuals, other studies found that the gut microbiota of obese people is characterized by an increase in the Firmicutes/Bacteroidetes ratio; as in Ukraine [25] and Italy [26]; while others even find an opposite relationship; as in China [27].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the family Prevotellaceae and genus Prevotella were positively associated with Fat% in both the placebo and HDP groups, despite the opposite directions of changes associated with the type of intervention. Prevotella is a strong marker of obesity ( Duan et al., 2021 ) and its function was not affected by probiotic therapy in our study. Barnesiellaceae abundance in the control group was significantly positively associated with end-point glucose concentration, and this unfavorable effect was not observed in groups receiving probiotics.…”
Section: Discussionmentioning
confidence: 47%
“…An increased abundance of Actinobacteria was also associated with type 2 diabetes in urban Africa (Doumatey et al, 2020). In contrast, another study showed that Actinobacteria levels decreased in obese individuals (Duan et al, 2021). The family Coriobacteriaceae plays important metabolic roles such as the conversion of bile acid, steroids, and phytoestrogens, glucose homeostasis, and lipid metabolism, and is associated with good metabolic health in overweight and obese populations (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At the family level, both MiHC and OMiAT identified Veillonellaceae , whereas aMiSPU, LDM, and OMiRKAT identified Lachnospiraceae . But, AMAT showed superiority by identifying both Veillonellaceae and Lachnospiraceae , which had been found to be associated with BMI in other studies as well ( 44 , 45 ). On the other hand, AMAT did not detect any significant genera, while Ruminococcaceae Incertae Sedis was identified by MiHC, and Lachnospiraceae Incertae Sedis was identified by aMiSPU, LDM, and OMiRKAT .…”
Section: Resultsmentioning
confidence: 80%